New insights on crinoid (Echinodermata; Crinoidea) bioluminescence - Mallefet, Jérôme; Martinez-Soares, Pablo; Eléaume, Marc; O’Hara, Timothy; Duchatelet, Laurent (Frontiers in Marine Science, 2023)
Bioluminescence in echinoderms has been known since the early 19th century. Of the four luminous classes known, Crinoidea is the least studied, with only five bioluminescent species reported. The research conducted during the RV Southern Surveyor 2005 "Mapping benthic ecosystems" and the RV Investigator 2017 "Sampling the Abyss" cruises aimed to systematically sample deep benthic habitats along Australia’s eastern and southwestern margins. These cruises allowed us to acquire the first in vivo pictures of light-emitting Crinoidea and luminometric measurements on fresh tissue samples. Four new records of bioluminescence in deep-sea Comatulida from three distinct clades, double the number of known Crinoidea species with bioluminescent capacity. In vivo photography and histology suggest that, in some species, light emission might originate from the sacculi. Pharmacological assays reveal that Thalassometridae light emission is under adrenergic control. Biochemical data indicate the presence of a coelenterazine-based luciferin-luciferase system in Thalassometra cf. gracilis similar to the one described in the ophiuroid Amphiura filiformis. Phylogenetic distribution of bioluminescence among Crinoidea and differences in this trait phenotype could be indicative of multiple acquisitions of luminescent capability in Crinoidea, possibly promoted by the ecological role that bioluminescence might fulfill in the vastness of the deep benthic habitat.